Human sexuality - Bolin, Anne, author.
1 online resource
Keywords: "This ground-breaking second edition of Human Sexuality continues its broad and interdisciplinary goal of providing readers with a comprehensive overview on sexuality as a core part of our individual identities and social lives. Utilizing viewpoints across cultural and national boundaries and taking into account the evolution of human anatomy, sexual behavior, attitudes, and beliefs across the globe, Human Sexuality 2nd edition remains an essential text for educators and students who wish to understand human sexuality in all of its richness and complexity"--